Sutureless Valve in Bicuspid Aortic Stenosis: Modified Technique and Midterm Outcome - Li, Han-Yan; Tsai, Feng-Chun; Lu, Cheng-Hui; Chou, An-Hsun; Huang, Huei-Chiun; Gersak, Borut (The Thoracic and Cardiovascular Surgeon, 2022)
Background The sutureless valve has gained popularity for degenerative aortic valve stenosis but not congenital bicuspid aortic valve (BAV) due to anatomical challenges. We reviewed our modified implant techniques for patients with BAV.Methods From June 2015 to June 2019, 66 patients with aortic valve stenosis were treated with the Perceval sutureless valve, 20 of whom had BAV. The demographics, type of BAV (the Sievers classification), and associated pathologies, surgical outcomes, and midterm hemodynamics were recorded.Results The median age was 64 (range: 49–81) years and the Society of Thoracic Surgeons score was 2.186 (range: 0.407–6.384). Annular plication was performed in 9 (75%) of 12 type 0 and 3 (37.5%) of 8 type I, with implanted valve sizes of M, L, and XL in 6, 10, 4 cases, respectively. Three patients, all type 0 in the initial learning periods, required intraoperative redeployment due to malposition of the valve. The final implant was successful in all without conversion to traditional prosthesis. The median extubation time was 4 hours and the durations of intensive care unit and hospital stay were 1 and 6 days. At a median follow-up of 46 (23–72) months, there was one late mortality due to hemorrhagic stroke sequel. The last echo revealed none had more than mild paravalvular leakage and the mean transvalvular pressure gradient remained stable at 9.70 (range: 6.94–15.0) mm Hg.Conclusion The sutureless valve can achieve satisfactory outcomes in BAV without paravalvular leakage and excellent hemodynamics. It may serve as the benchmark for transcatheter aortic valve implantation in this unique population.
Keywords: aortic valve stenosis; aortic valve replacement; congenital bicuspid aortic valve; Perceval sutureless valve